Acidity effects of medium fluids on anhydrous proton conductivity of acid-swollen block polymer electrolyte membranes. Issue 31 (26th May 2021) - Kajita, Takato; Noro, Atsushi; Seki, Takahiro; Matsushita, Yushu; Nakamura, Naoki
Abstract : Sulfuric acid-swollen block polymer membranes exhibit anhydrous conductivities of ∼0.1 S cm −1 that is higher than those of phosphoric acid-swollen membranes, whereas temperature dependence of conductivities of the latter is stronger than the former. Abstract : Proton-conductive polymer electrolyte membranes (PEMs) were prepared by infiltrating sulfuric acid (Sa) or phosphoric acid (Pa) into a polystyrene- b -poly(4-vinylpyridine)- b -polystyrene (S–P–S) triblock copolymer. When the molar ratio of acid to pyridyl groups in S–P–S, i.e., the acid doping level (ADL), is below unity, the P-block/acid phase in the PEMs exhibited a moderately high glass transition temperature ( T g ) of ∼140 °C because of consumption of acids for forming the acid–base complexes between the pyridyl groups and the acids, also resulting in almost no free protons in the PEMs; therefore, the PEMs were totally glassy and exhibited almost no anhydrous conductivity. In contrast, when ADL is larger than unity, the T g s of the phase composed of acid and P blocks were lower than room temperature, due to the excessive molar amount of acid serving as a plasticizer. Such swollen PEMs with excessive amounts of acid releasing free protons were soft and exhibited high conductivities even without humidification. In particular, an S–P–S/Sa membrane with ADL of 4.6 exhibited a very high anhydrous conductivity of 1.4 × 10 −1 S cm −1 at 95 °C, which is comparable to that of humidified Nafion membranes. Furthermore, S–P–S/Sa membranes with lower T g s exhibited higher conductivities than S–P–S/Pa membranes, whereas the temperature dependence of the conductivities for S–P–S/Pa is stronger than that for S–P–S/Sa, suggesting Pa with a lower acidity would not be effectively dissociated into a dihydrogen phosphate anion and a free proton in the PEMs at lower temperatures.